2009
DOI: 10.1038/nrn2571
|View full text |Cite|
|
Sign up to set email alerts
|

Identity crisis for adult periventricular neural stem cells: subventricular zone astrocytes, ependymal cells or both?

Abstract: A population of neural stem cells (NSCs) resides adjacent to the lateral ventricles in the adult mammalian brain. Despite knowledge of their existence since the early 1990s, their identity remains controversial, with evidence suggesting that they may be ependymal cells, glial fibrillary acidic protein (GFAP)-expressing subventricular zone (SVZ) cells or several distinct NSC populations. This issue has major implications for the therapeutic use of NSCs as well as for the study and treatment of brain cancers. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 151 publications
3
141
0
5
Order By: Relevance
“…2008; Chojnacki et al. 2009) migrating through a channel of interwoven astrocytes, the rostral migratory stream (RMS), to the olfactory bulb. The SVZ niche is separated from the cerebrospinal fluid (CSF) of the ventricles via a thin layer of multiciliated ependymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…2008; Chojnacki et al. 2009) migrating through a channel of interwoven astrocytes, the rostral migratory stream (RMS), to the olfactory bulb. The SVZ niche is separated from the cerebrospinal fluid (CSF) of the ventricles via a thin layer of multiciliated ependymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, GFAP is expressed in some nerve cell populations, including hippocampal neurons of older individuals (1). It is also expressed in some precursor populations of nerve cells as well as in cells that can give rise to both nerve and glia (2)(3)(4). Finally, the expression levels of GFAP within individual cells is extremely variable, and higher expression levels may limit the tumorigenicity of subpopulations of cells within glioblastomas (5,6).…”
Section: The Intermediate Filament Protein Glial Fibrillary Acidic Prmentioning
confidence: 99%
“…Without a doubt, the features shared by the many cellular types of the SVZ contributed to the debate about the true identity of NSCs (for review, Chojnacki et al, 2009). Mitotic cells (astrocytes or B cells) have been generally considered to be the true NSCs, owing to their self-renew capacity and their ability to indefinitely produce neuronal and glial progeny (García-Verdugo et al, 1998;Doetsch et al, 1999).…”
Section: The Svz and Rostral Migratory Stream (Rms): A General Viewmentioning
confidence: 99%
“…Most studies have not observed substantial changes in infarct size after NSCs transplantation (Kelly et al, 2004;Pollock et al, 2006); however, neuroprotective (Lee et al, 2007;Ourednik et al, 2002) and immunomodulatory (Fujiwara et al, 2004;Pluchino et al, 2005) effects of NSCs in addition to their potential for at least some cell replacement (Sinden et al, 1997), have collectively yielded beneficial effects in multiple animal models of neurodegeneration and brain injury, including stroke (Chu et al, 2004;Pollock et al, 2006;Sinden et al, 1997).…”
Section: From Theory To Practice: Nscs Transplant In Rodent Models Ofmentioning
confidence: 99%